SOCIAL MEDIA-DRIVEN PROCESS INNOVATION AND COMPETITIVE ADVANTAGE IN ART GALLERIES AND MUSEUMS: THE MEDIATING ROLE OF VISITOR CO-CREATION - Radiany, Ade Asria; Herdinata, Christian; Kodrat, David Sukardi (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
The purpose of this study is to analyze the influence of social media-driven process innovation on competitive advantage in art galleries and museums, with visitor co-creation as a mediating variable. Drawing on Dynamic Capability Theory (DCT), the study employs a quantitative design with PLS-SEM on 198 valid responses from Cultural and Creative Industry organizations registered with Indonesia"™s Creative Economy Agency (Bekraf), following rigorous validation through expert review, pilot testing, and screening procedures. Results show social media-driven process innovation significantly affects visitor co-creation (Î² = 0.793, p < 0.001) and competitive advantage (Î² = 0.258, p = 0.010). Visitor co-creation also strengthens competitive advantage (Î² = 0.595, p < 0.001). Mediation testing confirms partial mediation with VAF = 64.7%. The model explains 62.8% of the variance in visitor co-creation and 55.2% in competitive advantage. These findings offer practical implications for cultural institutions by highlighting the strategic importance of integrating digital innovation with visitor engagement to achieve sustainable competitiveness. JEL: M21, M531, M537.